Elaboración de un manual de funciones, valoración de puestos por puntos y reglamento de admisión y empleo para la fundación ser de la ciudad de Loja. - Arellano Luna, Karla Belén (2014)
This research thesis main objective was "Development of a manual functions, job evaluation points and rules for admission and employment for the foundation" BE "in the city of Loja", allowing efficient administration in the foundation, which gave rise to the title of this work. Summary as point b, where each part of the thesis is presented below disintegrates; then comprises the introduction, where an overview of the problems that gave rise to the thesis topic is given. Literature review that contains components that substantiate the thesis topic theoretically with other authors' arguments that support the knowledge mentioned in this research paper presents the point d. Then at the point e, the materials and methods where the use of the methods, a scientist who was used to obtain information used for the theoretical framework highlights are presented; deductive whereby information related to human talent was collected; for inductive analysis of the data obtained through research techniques such as interview the Director and employee survey currently working on the foundation that allowed gathering valuable information about the development of human talent; history through which he could make the historical review of the company; description, by which it was possible to show the structure or behavior of the Foundation; analytical than was used when examining the information provided surveys and interviews. Also direct observation techniques to get the first impression about the infrastructure and development of human resources in the company were applied; and interview the Director applied function and survey of employees of the same in a total of 30. In the results begins with a historical overview of the company, then as part of the diagnostic recording the results of surveys and interview the manager and employees of the foundation "SER", respectively. The results of this research allowed the development of restructured organizational chart where consist charges are based on the current situation of the company, then a manual where valuable features and important information is presented with respect to each developed charges that make up the business, functions and responsibilities of the members of the organization, avoiding duplication of functions and enabling better business organization. Besides the valuation of positions, where the system is applied on points with their respective stages from defining factors to the valuation of jobs, where the following results were obtained was developed: the total points as the valuation is 4355, salaries paid to employees of the company amounted to $ 6,927.59, with these data the straight line equation was applied, which resulted in a slope of 1.59, based on the above value, the wage adjustment was made a recovery factor of 1.59, in order to determine the new salaries. Note that this revaluation was performed only charges that were below the line of the salary adjustment, which in total amounted to 7 and are Director, Accountant, Internist Receptionist Laboratorista, Gynecologist and Assistant Pharmacy. Completing this point the rules for admission and employment was given it will allow the company to select the most suitable for any office where a vacancy arises in future staff. Finally, conclusions and recommendations of the paper are presented the most relevant to human talent working in the foundation "SER" unknown key tasks or job functions and requirements that the position, due to the lack of a description and analysis at each job, and within the recommendations we suggest considering Manual of Classification and Valuation of positions for the company, with the aim of systematically evaluate staff performance in office, which will determine whether meets the requirements necessary for the various positions in the company.